Pengaruh Bahan Pengisi Terhadap Kelarutan Dan Sifat Organoleptik Minuman Instan Dari Limbah Cair Buah Merah - Albert Amsamsyum; Budi Santoso; Eduard Fransisco Tethool (Fakultas Pertanian Universitas Papua, 2012)
This study aims to determine the characteristics of the instant drink from wastewater of red fruit oil extraction. Experimental method was used in this study. This study consisted of three phases: (1) Analysis of the chemical composition of red fruit wastewater, (2) Formulation of instant drinks and (3) organoleptic testing. The treatment in this study was the use of fillers ingradients : CMC with a concentration of 0.5, 0.75 and 1% and Dextrin with a concentration of 0.5, 0.75 and 1%. Data were collected for chemical composition of wastewater red fruit, solubility and panelist preferences for color, flavor and aroma of instant drinks product. The results showed that red fruit wastewater contains 5.95% carbohydrates, 7.83% fat; 4.03% protein; 0.63% ash, 14.5 mg/100g Vitamin C; and 32.71 ppm for total carotenoids. Solubility of red fruit wastewater instant drink was ranged between 98-99%, and organoleptic test results showed that the highest obtained in instant drinks with added Dextrin 0.5% as a filler ingredients (score 3.56) while the lowest obtained in instant drinks with CMC 1% as a filler ingredients (score 2.79).